Evolução da indústria de private equity e venture capital no Brasil: uma análise de desempenho das cotas de FIP’s - Alves, Samuel Marcelo Ferreira (2022)
The object of the research is the analysis of the performance of FIP’s quotas through an econometric model. The methodology consists of the analysis through the log and annualized return of the shares in panel data from a sample of 84 FIPS in the period between 2003 and 2020.Independent variants, were used: PL, Investment Size, Investment Number (amount), Performance and, Result of the Exercise. The results demonstrate that, although statistically significant, they were not fully conclusively to affirm that the independent variables are determinant in the increasing or decreasing performance of FIP values as a function of investment, whereas descriptive statistics presented limitations for not assessing relevant qualitative aspects that can explain the performance of FIPs, such as the effect of intellectual capital on management of startups due to the difficult measurement of their impact on results.